Penambahan Inokulum yang Berbeda pada Ampas Tebu Fermentasi Terhadap Kualitas Nutrisi - Jepri Juliantoni; Triani Adelina; Irdha Mirdhayati; Ayu Sri Afriani (Musamus Journal of Livestock Science, 2023)
Sugarcane bagasse is an agricultural waste that could be processed into ruminant alternative feed. Sugarcane bagasse processing was very necessary to improve the nutritional as animal feed using fermentation application which was one way to increase the nutritional of sugarcane bagasse using cow feces inoculum and EM-4 (Effective Microorganism-4). The purpose of this study was to determine the effect nutritional quality of fermented sugarcane bagasse using different types of inoculum. This study used a Completely Randomized Design (CRD) with 4 treatments and 5 replications that are ; P0: sugarcane bagasse without inoculum addition (control), P1: sugarcane bagasse + 5% cattle feces, P2: sugarcane bagasse + EM-4 10%, P3: sugarcane bagasse + 5% cattle feces + E-4 10%. The parameters measured include dry content, crude protein, crude fiber, and crude fat. The data were analyzed using Analysis of Variance (ANOVA) and continued with Duncan’s Multiple Range Test (DMRT). The results showed that a mixture of 5% cow feces and 10% EM-4 had a very significant effect (P <0.01) to increase crude protein ​​and significantly (P <0.05) to reduce crude fiber. The conclusion of this research was the addition of 5% cow feces inoculum and 10% EM-4 (P3 treatment) was the best treatment because it increased crude protein content and decreased crude fiber